PEER COUNSELING TRAINING TO IMPROVE THE COMPETENCE OF SOPHOMORE PEER COUNSELORS - Ema Zati Baroroh; Kiki Amalia (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
Counseling training programs need to be held because there is still a lack of student skills related to this program. Thus the competence of peer counselors needs to be improved. This training program's purposes are to provide participants with new knowledge and insight regarding the treatment of peer counselors. The research sample was 47 students undergraduate. The experimental design used is One Group Pre-test and Post-test Design. This training was held in two days with different durations. The research methods used here were mixed methods. The qualitative data were gained through a self-reflection form. Then, the quantitative data were taken through a knowledge test. The result of the Quantitative test was based on the analysis of the Paired sample T-Test, the result is p = 0.00 (p < 0.01). This implies that there is a clear difference before and after the training program. As can be seen from the qualitative results, the majority of the participants have experienced positive changes which can be detected in the self-reflection form exclusively in the section of new skills, skill upgrades, insights, and impressions. In the end, this article discusses findings, limitations, and recommendations for further peer counselor research and training program.